Phytoplasma-conserved phyllogen proteins induce phyllody across the Plantae by degrading floral MADS domain proteins - Kitazawa, Yugo (J Exp Bot, 2017)
ABCE-class MADS domain transcription factors (MTFs) are key regulators of floral organ development in angiosperms. Aberrant expression of these genes can result in abnormal floral traits such as phyllody. Phyllogen is a virulence factor conserved in phytoplasmas, plant pathogenic bacteria of the class Mollicutes. It triggers phyllody in Arabidopsis thaliana by inducing degradation of A- and E-class MTFs. However, it is still unknown whether phyllogen can induce phyllody in plants other than A. thaliana, although phytoplasma-associated phyllody symptoms are observed in a broad range of angiosperms. In this study, phyllogen was shown to cause phyllody phenotypes in several eudicot species belonging to three different families. Moreover, phyllogen can interact with MTFs of not only angiosperm species including eudicots and monocots but also gymnosperms and a fern, and induce their degradation. These results suggest that phyllogen induces phyllody in angiosperms and inhibits MTF function in diverse plant species.